Efferent suppression of transien-evoked otoacustic emissions and speech discrimination in noise - Fuente C., Adrian; Hormazábal R, Ximena; López M., Alison; Bowen M., Macarena (Revista Chilena de Fonoaudiología, 2011)
The medial olivo-cochlear bundle has been widely studied in experimental animals and clinically, in human subjects. It has been suggested that one of the functions of this bundle relates to the discrimination of speech in the presence of background noise. No systematic studies of possible associations between the efferent suppression of otoacustic emissions (OAEs) and performance on speech-in-noise tasks has been carried out. For this reason, we are investigating the amplitude of the efferent suppression of OAEs and how this may be associated with performance on speech-in-noise tasks. The results of a pilot study on this topic are addressed in this manuscript. A total of 45 normal-hearing adult subjects were studied. Transient-evoked OAEs (TEOAEs), the efferent suppression of TEOAEs, ipsi and contralateral acoustic reflexes (0.5, 1, 2, and 4 HHz) were obtained and the hearing-in-noise-test (HINT) was administered to all the subjects selected. No significant differences were found in the efferent suppression of TEOAEs between ears. No significant correlations between results for the efferent suppression of TEOAEs and those for the HINT were found. These results and the need for further research are discussed.